Incidence of apical leaf curl disease (ToLCNDV), and economics and reaction of potato (Solanum tuberosum) cultivars against whitefly, Bemisia tabaci in northern India - BHATNAGAR, ANUJ; PANT, R P; SRIDHAR, J; CHAKRABARTI, S K; LAL, MURARI (The Indian Journal of Agricultural Sciences, 2017)
Whitefly transmissible Gemini virus, Tomato leaf curl New Delhi virus-potato (ToLCNDV-potato) causing potato apical leaf curl disease has been posing serious threat to both seed and ware potato production in northern India. Two sets of field and laboratory experiments were conducted to assess the incidence of Bemisia tabaci and ToLNDV-potato under sprayed and unsprayed conditions of nine most commonly cultivated potato varieties during two consecutive years. Besides, that varietal response to B. tabaci and ToLCNDV-potato was also evaluated. The whitefly population significantly varied on potato cultivars sprayed and unsprayed conditions. Minimum incidence of B. tabaci was recorded in Kufri Bahar (5.0/5 plant) and Kufri Khyati (7.0/ 5 plant) when crop was sprayed by three insecticide sprays. The maximum incidence of whitefly (15.33/5 plant) was recorded in Kufri Pukhraj followed by Kufri Chipsona-1 (15.0/5 plant) when crop remain unsprayed. The higher population of whitefly was recorded in the year 2013-14 as compared to 2014-15. The maximum yield and highest cost: benefit ratio was found in the three sprays treatment of cv. Kufri Khyati followed by Kufri Garima. PCR results revealed that most common 22 potato cultivars grown in the country acquired ToLNDV-potato in due course of time, however some of potato cultivars like Kufri Anand, Kufri Chandramukhi, Kufri Chipsona 1, Kufri Chipsona 2, Kufri Chipsona 4, Kufri Gaurav, Kufri Himalini, Kufri Khyati, Kufri Pukhraj and Kufri Satlej acquired ToLNDV-potato very quickly and showed positive reaction in of October. The sample of whitefly drawn from the respective potato cultivars in of October also exhibited positive reaction as per retaining the virus with almost same trend of potato cultivars. Thus, it is concluded that potato cultivars must be well protected using Imidacloprid followed by Thiamethoxam and Imidacloprid insecticides, first spray on 20 days after planting followed by second and third sprays on 35 and 42 days after planting, respectively for suppression of whitefly population and effective management of apical leaf curl disease, especially crop grown for seed purpose.